2013
DOI: 10.1097/jpo.0b013e31829a965c
|View full text |Cite
|
Sign up to set email alerts
|

Residual Muscle Contraction and Residuum Socket Interface Force in Men with Transtibial Osteomyoplastic Amputation

Abstract: In the transtibial osteomyoplastic amputation (TOA) technique, the distal ends of the tibia and fibula are surgically joined to form a ''bone bridge'' to stabilize the bony anatomy of the distal residuum. The distal-most muscles also are secured to reestablish a length-tension relationship. Unlike conventional amputation techniques in which the muscles are not secured and do not retain length-tension relationship, the TOA procedure is anticipated to allow muscles to actively contract and retain normal physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Gait and weight distribution symmetry could help prevent overuse to the contralateral limb of the prosthesis user. 31,32 Furthermore, daily and chronic volume fluctuations may affect the quality of prosthesis comfort and use. During volume loss, it is crucial that the RL be able to tolerate the redistribution of pressure, particularly to the distal end, while not creating excessive pain or cause for skin breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gait and weight distribution symmetry could help prevent overuse to the contralateral limb of the prosthesis user. 31,32 Furthermore, daily and chronic volume fluctuations may affect the quality of prosthesis comfort and use. During volume loss, it is crucial that the RL be able to tolerate the redistribution of pressure, particularly to the distal end, while not creating excessive pain or cause for skin breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Gwinn et al reported the preoperative differences between the bone bridging and non-bone bridging transtibial amputation in patients who sustained a wartime blast injury. Gwinn et al reported an average age of 23.5 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) years. Functional level and prosthesis accommodation of the subjects were not reported.…”
Section: Perioperative Carementioning
confidence: 99%
“…Vital signs and reports of perceived exertion were recorded to ensure participant safety ( 13 ). Pressure and muscle activation data were collected using the OU-PAM ( 3 , 14 ), which can capture 16 analog input channels at 1 kHz. It utilizes the STK525 ( 15 ) and ATEVK525 ( 15 ) boards for data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Active gait performance is the primary, expected outcome ( 7 ). Mai et al ( 3 ) documented novel muscle activity in the distal OTTA residuum, and Dionne et al ( 8 , 9 ) found comparable work performance (gait, lifting, and carrying) in these same male participants with OTTA, as intact controls. Thus, investigators expected that men with OTFA would perform better or similar to controls, despite missing a knee joint system, shank, ankle joint system, and foot ( 4 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation